A global high shift scenario. The potential for dramatically increasing bicycle and e-bike use in citites around the world, with estimated energy, CO2, and cost impacts. - Mason, Jacob; Fulton, Lew; McDonald, Zane (My University, 2015)
Cycling plays a major role in personal mobility around the world, but it could play a much bigger role. Given the convenience, health benefits, and affordability of bicycles, they could provide a far greater proportion of urban passenger transportation, helping reduce energy use and CO2 emissions worldwide.1 This report presents a new look at the future of cycling for urban transportation (rather than recreation), and the potential contribution it could make to mobility as well as sustainability. The results show that a world with a dramatic increase in cycling could save society US$24 trillion cumulatively between 2015 and 2050, and cut CO2 emissions from urban passenger transport by nearly 11 percent in 2050 compared to a High Shift scenario without a strong cycling emphasis.
Keywords: Individualverkehr; Fahrradverkehr; Nachhaltigkeit; Elektromobilität; Fahrradnutzung; Fahrradbenutzung; Studie